Sustainable Cultivation of Desmodesmus armatus SAG276.4d using Leachate as a Growth Supplement for Simultaneous Biomass Production and CO2 Fixation - Muhammad Taufiq Kamal Fuad; Azianabiha A Halip Khalid; Kamrul Fakir Kamarudin (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Microalgae cultivation has been identified to be highly beneficial for the production of valuable biomass. The recent worldwide interest is to cultivate microalgae in wastewater to replace the use of expensive commercial media. Microalgae can utilize nutrients from the wastewater for their biomass growth, which is useful as feedstock in many products. Interestingly, microalgae cultivation is also capable of reducing a greenhouse gas due to absorption of carbon dioxide (CO2) during photosynthesis. This study was conducted to study the growth of microalgae using leachate as a nutrient supplement. The scope of the research involved the cultivation of freshwater microalgae, Desmodesmus armatus, in the synthetics medium with various percentages of leachate under different light exposures. The growth parameters such as the specific growth rate, biomass productivity, and cell division time were used to evaluate the microalgae growth performance. The amount of CO2 absorbed during the cultivation was determined based on the total biomass production. The highest growth rate of 0.423/day was achieved using a 5% leachate medium under 12 h light duration, and the highest carbon fixation of 1.317 g CO2/L/day was calculated using a culture supplemented with 5% leachate with 24 h light period. The high presence of nutrients in the leachate has contributed to the growth of the microalgae; thus, it has great potential as an alternative growth medium to support biomass production and subsequently help to mitigate global warming.